2022
DOI: 10.1093/brain/awac418
|View full text |Cite
|
Sign up to set email alerts
|

Anti-pan-neurofascin antibodies induce subclass-related complement activation and nodo-paranodal damage

Abstract: Autoimmune neuropathy associated with antibodies against pan-neurofascin is a new subtype of nodo-paranodopathy. It is relevant because it is associated with high morbidity and mortality. Affected patients often require intensive care unit treatment for several months, and data on the reversibility and long-term prognosis are limited. The pathogenicity including IgG subclass-associated mechanisms has not been unraveled, nor been directly compared to anti-neurofascin-155 IgG4 related pathology. Understanding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 94 publications
0
45
0
Order By: Relevance
“…An antibody against the glial neurofascin isoform, NF155, was predominantly of IgG4 subtype, which lacks the ability to activate a conventional complement-mediated or cellular immune response. A recent study revealed that anti-NF155 IgG4 was pathogenic because it rendered NF155 degeneration directly, whereas the anti-NF186 antibody may be more widely distributed in different antibody isotypes or IgG subtypes, and it may be pathogenic in a complement dependent manner, similar to the pathogenic mechanism of anti-pan-neurofascin antibody [ 6 , 22 ]. This may also be the underlying mechanism of the effective glucocorticoids and IVIG treatment as shown by both this study and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…An antibody against the glial neurofascin isoform, NF155, was predominantly of IgG4 subtype, which lacks the ability to activate a conventional complement-mediated or cellular immune response. A recent study revealed that anti-NF155 IgG4 was pathogenic because it rendered NF155 degeneration directly, whereas the anti-NF186 antibody may be more widely distributed in different antibody isotypes or IgG subtypes, and it may be pathogenic in a complement dependent manner, similar to the pathogenic mechanism of anti-pan-neurofascin antibody [ 6 , 22 ]. This may also be the underlying mechanism of the effective glucocorticoids and IVIG treatment as shown by both this study and other studies.…”
Section: Discussionmentioning
confidence: 99%
“…The course was usually monophasic. Some patients improved with IVIg, but showed a fulminant relapse in few days/weeks 37 . Response to plasmapheresis was partial and not sustained; response to corticosteroids was poor.…”
Section: Nodo‐paranodopathiesmentioning
confidence: 97%
“…Response to plasmapheresis was partial and not sustained; response to corticosteroids was poor. The mortality in patient with antibodies to panNF was high even though some patients showed spontaneous remission 37 . After responses to standard treatment were deemed inadequate (often several months into the illness) the surviving patients received rituximab with a good response till to functional independence.…”
Section: Nodo‐paranodopathiesmentioning
confidence: 99%
“…Another type of auto antibodies targeting the paranode is anti‐pan neurofascin (panNF), which recognize both glial and neuronal isoforms of neurofascin. As these antibodies can target both nodes and paranodes, it is not surprising that the affected patients present with the most severe nodopathy 92 . Starting as GBS with a short recovery, they then develop a severe disease with tetraplegia, autonomic instability, cranial nerve involvement, respiratory failure, and a high mortality.…”
Section: Diseases Involving Components Of the Paranodal Axoglial Junc...mentioning
confidence: 99%
“…As these antibodies can target both nodes and paranodes, it is not surprising that the affected patients present with the most severe nodopathy. 92 Starting as GBS with a short recovery, they then develop a severe disease with tetraplegia, autonomic instability, cranial nerve involvement, respiratory failure, and a high mortality. Anti-NFpan antibodies can activate complement in vitro.…”
Section: Immune-mediated Paranodopathiesmentioning
confidence: 99%